2018
DOI: 10.1002/jclp.22713
|View full text |Cite
|
Sign up to set email alerts
|

The stigmatization of nonsuicidal self‐injury

Abstract: Objectives: Despite the high prevalence of non-suicidal self-injury (NSSI), no research has systematically studied the occurrence and effects of stigmatization by others towards NSSI scarring. Method: The current study measured implicit and explicit attitudes among undergraduates towards NSSI scarring using the Implicit Association Test and questionnaires to compare implicit and explicit biases towards NSSI with biases towards tattoos, a culturally-sanctioned form of self-determined marking, as well as non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 75 publications
3
49
0
4
Order By: Relevance
“…It has also been suggested that males may present with a different clinical picture, including lower reported severity levels of self-harm correlates [23]. Self-harm has a history of being thought of as a problem mainly affecting females [24], but reporting levels may also be influenced by perceived stigma [25,26] as well as professional bias based on assumptions of sex difference. It is possible that SH in males to a larger extent run undetected or is misconceived, diminishing the strength of the association between SH in males and the different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that males may present with a different clinical picture, including lower reported severity levels of self-harm correlates [23]. Self-harm has a history of being thought of as a problem mainly affecting females [24], but reporting levels may also be influenced by perceived stigma [25,26] as well as professional bias based on assumptions of sex difference. It is possible that SH in males to a larger extent run undetected or is misconceived, diminishing the strength of the association between SH in males and the different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although not always associated with suicide risk, NSSI (especially repetitive and severe self-injury) is one of the strongest independent predictors of future suicide attempts [16][17][18][19], and is associated with severe role impairment in daily life [9], stigma and feelings of shame [20,21], low levels of help-seeking [22,23], and poorer academic performance [24]. These findings underscore the necessity to address and respond to NSSI among college students [25].…”
Section: Introductionmentioning
confidence: 98%
“…Pooled lifetime prevalence estimates of NSSI are close to 17%-18% among adolescents and 12%-20% among emerging adults (3,4). NSSI behaviors are an important predictor of future suicidal thoughts and behaviors (5)(6)(7)(8) and psychopathology (9,10), and are associated with stigma and feelings of shame (11)(12)(13), low levels of disclosure and help-seeking (14)(15)(16), and other adverse outcomes [e.g., poorer academic performance; (17)]. Together, these findings underscore the importance of a good understanding of the factors that underlie NSSI, with a view to informing preventive and intervention initiatives.…”
Section: Introductionmentioning
confidence: 99%